2011
DOI: 10.1007/s00421-011-1826-2
|View full text |Cite
|
Sign up to set email alerts
|

Red grape leaf extract improves endurance capacity by facilitating fatty acid utilization in skeletal muscle in mice

Abstract: Improving endurance capacity leads to increased athletic performance and active lifestyles. The aim of this study was to investigate the effect of the intake of red grape leaf extract (RGLE), used as a traditional herbal medicine in the Mediterranean area, on endurance capacity in mice. Male BALB/c mice were divided into three experimental groups with similar swimming times and body weights; control group, 0.2% (w/w) and 0.5% RGLE group. Swimming times were measured for evaluation of endurance capacity once a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(38 reference statements)
2
14
0
Order By: Relevance
“…Numerous investigations reported medical applications of RVLE [17], for example, treatments for chronic venous insufficiency over many decades [16, 18]. Besides, it could also improve endurance capacity by facilitating fatty acid utilization in skeletal muscle in mice [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations reported medical applications of RVLE [17], for example, treatments for chronic venous insufficiency over many decades [16, 18]. Besides, it could also improve endurance capacity by facilitating fatty acid utilization in skeletal muscle in mice [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Animal and in vitro model studies have shown that Cy3G has anti-obesity13 and anti-diabetic effects1314. Additionally, the supplementation of red grape leaf extract containing Cy3G has been reported to enhance exercise capacity by activating fatty acid oxidation15. Furthermore, in human clinical trial done by Mazza G et al 16.…”
mentioning
confidence: 99%
“…Green tea extract and red grape leaf extract, which contain a lot of phenolic compounds, were beneficial for improving exercise capacity (3,36). Extracts from plant leaves contain abundant amounts of phenolic compounds, which act as antioxidants, and may have beneficial effects on exercise performance (3,10,12).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous antioxidants may prevent exercise-induced oxidative damages, since they are able to detoxify certain free radicals and peroxides with enhancing endogenous antioxidants (12)(13)(14). In addition, antioxidants from plant-leaf may improve physiological conditions by promoting and interacting with endogenous antioxidants (3,10,12). Thus, antioxidants can be key elements to combat and reduce the degree of exhaustion.…”
mentioning
confidence: 99%
See 1 more Smart Citation